OP0332 COMPLEMENT FACTOR EXPRESSION AND ACTIVATION IN OSTEOARTHRITIS JOINT COMPARTMENTS. (June 2019) - Assirelli, Elisa; Pulsatelli, Lia; Dolzani, Paolo; Addimanda, Olga; Lisignoli, Gina; Mariani, Erminia; Meliconi, Riccardo
Abstract : Background: Several studies have identified a central role for the activation of the complement system in the pathogenesis of OA, finding an abnormally high expression and activation of complement in human osteoarthritic joints and the specific contribution of complement (C) components 5 and 6 and the membrane attack complex (MAC) (1). The complement system consists of several proteins which contribute to an enzymatic cascade ending in lysis. Two main, different pathways converge into C3 factor activation. In the classical pathway C4 is involved, while in alternative pathways Factor-b (FB) is involved. Objectives: The aim of this study was to investigate the expression of complement factors (C3, C4 and FB) and activation fragments (C3a, C5a, FBa, MAC) in OA joint tissues. Methods: Osteochondral biopsies from 33 patients (16 OA, 12 Rheumatoid Arthritis-RA and 15 Postraumatic cases-PT) who underwent knee, hip or shoulder arthroplasty were collected. Immunohistochemistry and quantitative Imaging analysis were perfomed to analyze C3, C4 and CFB expression. Cartilage pathology was evaluated utilizing Mankin score. Chondrocytes, synoviocytes, cartilage and synovial biopsies were obtained from 11 OA patients undergoing joint replacement surgery. Cultures were set up with or without pro-inflammatory (IL-1beta) stimulus. Culture supernatants were analyzed for C3a, C5a, CFBa and C5b-9 production using enzyme-linked immuno-sorbent assay (ELISA). Statistical analysis was performed utilizing Wilcoxon matched pairs test and Mann Whitney's test, using Graph Pad Prism software. Results: In osteochondral biopsies, C factor expression was located in bone marrow and in a few subchondral bone cells. C3 was the most expressed factor in all patient subtypes while factor C4 had a very low expression, except for some sporadic cases. (OA: C3 vs FactorB p=0.0280, C3 vs C4 p=0.0005; RA: C3 vs FactorB p= 0.0269, C3 vs C4 p=0.0005; PT: C3 vs FactorB p=ns, C3 vs C4 p=0.0001) CFB was significantly augmented in PT and was not significantly different between OA and RA. C factors expression did not correlate with Mankin score or with the joint type (knee, hip or shoulder). Cell positivity was mainly present in the subchondral bone (bone marrow) whereas cartilage was almost negative. As to activation fragments, C3a was the most produced factor (vs C5a and CFBa p<0.0005) but no differences were found between cultured chondrocytes and synoviocytes (vs synovial tissue p<0.0005) and its production was not stimulated by proinflammatory stimulus. C5a production in cartilage was significantly higher than in chondrocytes and synovial tissue (both p<0.0005) but no differences were found between cartilage and synoviocytes. CFBa was induced by IL-1beta in synovial tissue. C5b-9 production was undetactable in chondrocytes and synoviocytes cell culture supernatants. In cartilage C5b-9 production was decreased by IL-1 beta stimulus while in synovium it was increased, although not significantly. Conclusion: Complement factors were expressed mainly in bone marrow and in a few subchondral bone cells, but not in cartilage. Complement activating fragments are produced by chondrocytes and synoviocytes. The dissimilar expression of activating fragments by different cell types could suggest various C activating mechanisms in joint tissues. Reference: [1] Wang Q, et al. Nat Med 2011;17:1674-1679. Disclosure of Interests: None declared